Sustained censorship in MM (2026-06) (Myanmar) - Voidly (2026)
CRITICAL severity censorship detected in Myanmar. Confidence: 77%. Data sourced from OONI, CensoredPlanet.
Censorship Incident ID: MM-2026-0212
Keywords: censorship; MM; censorship; critical